A Stirling generator with multiple bypass expansion for variable-temperature waste heat recovery. (1st January 2023) - Jiang, Zhijie; Xu, Jingyuan; Yu, Guoyao; Yang, Rui; Wu, Zhanghua; Hu, Jianying; Zhang, Limin; Luo, Ercang
Highlights: A Stirling generator with bypasses for distributed-temperature waste heat recovery is proposed. Multiple-bypass structure is used to perform multiple heat-to-power conversion processes. The effects of crucial parameters on system performance are then presented. Electrical power increases by 29.3% when compared to the traditional Stirling generator. Abstract: Recovery heat from exhaust gas is a promising field in the context of global deepening of energy conservation and emission reduction. Small scale and cascade temperature variation make the exhaust gas waste heat recovery difficult. In order to make full use of the exhaust gas waste heat, a novel Stirling generator with a multiple-bypass configuration is proposed to fulfill the demand for recovery over a wide and continue temperature range. The exhaust gas is simplified into variable-temperature heat resource (VTHS, heat release accompanied by a decrease in temperature) and the cascade heat exchangers in the proposed system are assumed to converse heat with VTHS absorption continuously. In this paper, the ideal power efficiency of an infinite-stage generator is calculated. Then, a model of a 3-stage Stirling generator is established in software Sage. Theoretical analyses, exergy analyses and parameters analyses are carried out. The performance comparison between single-stage, 2-stage and 3-stage is presented at last. The result represents a significant increase by 29.3% in electric power when compared to the traditional single-stage system. These findings suggest a novel promising energy conversion technology for cascade utilization of exhaust gas waste heat.